2012
DOI: 10.1108/17570971211241903
|View full text |Cite
|
Sign up to set email alerts
|

Affective awareness in parenting of fathers with co‐occurring substance abuse and intimate partner violence

Abstract: Purpose-Few studies have examined the parenting of fathers with co-occurring Substance Abuse (SA) and Intimate Partner Violence (IPV) problems. None have specifically interviewed men with these co-occurring issues using qualitative methods about their reflective functioning in relation to their children. This qualitative study was designed to provide evidence of the reflective capacity of fathers with co-occurring SA and IPV.Approach-To assess this, men were asked to describe examples of negative emotions they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Is possible that in this case, boosted anger recognition in men with a history of partner aggression is linked to the experience of similar feelings during the VR scene as those experienced by children when exposed to real-life violence. This is relevant in light of past research showing that men who have perpetrated IPV have difficulties in taking the perspective of their children or the victims and frequently lack awareness of the negative impact that their aggressive behaviors may have on their family (Labarre et al, 2016; Maliken & Katz, 2013; Stover & Spink, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Is possible that in this case, boosted anger recognition in men with a history of partner aggression is linked to the experience of similar feelings during the VR scene as those experienced by children when exposed to real-life violence. This is relevant in light of past research showing that men who have perpetrated IPV have difficulties in taking the perspective of their children or the victims and frequently lack awareness of the negative impact that their aggressive behaviors may have on their family (Labarre et al, 2016; Maliken & Katz, 2013; Stover & Spink, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that males who have perpetrated intimate partner violence (IPV) find it difficult to take their children’s perspective, and that they lack awareness of the negative impact that their aggressive behaviors may have on their children (Stover & Spink, 2012). For instance, parents with a history of domestic violence tend to punish and intimidate their children when they display vulnerable emotions such as sadness or fear (Maliken & Katz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that fathers who are violent towards their partners may have a strong desire to be good fathers to their children. They are keen to be involved with their children and develop and maintain secure and close relationships with them (Perel & Peled, 2008 ; Salisbury, Henning, & Holdford, 2009 ; Stover & Spink, 2012 ). Some of the men in our study have little contact with their children and contact that is under supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Less isunderstood about how ACES impact fathers’ RF and how these may be associated with father–child interactions or fathers’ parenting. Fathers who have used IPV behaviors have significantly higher likelihood of having experienced child maltreatment or ACES and these have been correlated with poor RF (Stover & Spink, 2012; Mohaupt & Duckert, 2016) indicating a need to further understand the unique contributions of ACES and paternal RF to father–child interactions, especially with fathers who have used IPV behaviors.…”
Section: Introductionmentioning
confidence: 99%